Eksplorasi Etnomatematika Pada Budaya Banyumasan Sebagai Sumber Belajar Matematika - Oktaviani, Tamia; Sholihah, Dyahsih Alin; Wafa', Muhammad (Universitas Alma Ata, 2022)
Indonesia is an archipelagic country that has various types of culture, one of which is Java. In central Java, especially in Banyumas it’s famous for the Banyumasan Batik culture, the Begalan and Ebeg traditions in which there are elements and mathematical concepts. However, not many people use Banyumasan culture to serve as a learning resource in mathematics learning at school. This study aims to (1) fine out the fundamental mathematical activities found in Banyumasan Batik culture, the Begalan and Ebeg traditions, (2) fine out the ethnomathematical elements and concepts contained in Banyumasan Batik, Begalan and Ebeg traditions (3) and describe the use of ethnomathematical exploration results in Banyumasan Batik, Begalan and Ebeg traditions so that they can be used as a source of learning mathematics. The type of research used is qualitative research with an ethnographic approach. Data obtained from the results of interviews and documentation observations. The instrument in this study consisted of the main instrument, namely the researcher himself and the supporting instruments in the from of observation and interview guidelines and documentation tools. The data validity technique used in this study used a triangulation method with data analysis in the from of data reduction, data presentation and drawing conclusions. The results in this study are six fundamental mathematical activities in Banyumasan Batik culture, the Begalan and Ebeg traditions namely aspects of counting, measuring, locating, designing, playing and explaining. The mathematical elements and concepts found in Banyumasan Batik culture, the Begalan and Ebeg traditions are points, lines, similarity, parallelism, congruence, flat shapes (square, rectangle, triangle, trapezoid and circle), spatial shapes (cones and spheres), transformations (reflection, rotation and dilation). Utilization of the results of the ethnomathematical exploration in Banyumasan Batik, Begalan and Ebeg traditions can be used as a source of learning in school ranging form elementary to high school.Keywords : ethnomathematic, culture, banyumasan, learning resources,